Incidence of coronary artery disease in patients with valvular heart disease. Issue 6 (December 1980) - Morrison, G W; Thomas, R D; Grimmer, S F; Silverton, P N; Smith, D R
Abstract : The case notes, cardiac catheterisation data, and coronary arteriograms of 239 patients investigated for valvular heart disease during a five year period were reviewed. Angina present in 13 of 95 patients with isolated mitral valve disease, 43 of 90 patients with isolated aortic valve disease, and 18 of 54 patients with combined mitral and aortic valve disease. Significant coronary artery disease was present in 85 per cent of patients with mitral valve disease and angina, but in only 33 per cent of patients with aortic valve disease and angina. Patients with no chest pain still had a high incidence of coronary artery disease, significant coronary obstruction being present in 22 per cent with mitral valve disease, 22 per cent with aortic valve disease, and 11 per cent with combine mitral and aortic valve disease. Several possible clinical markers of coronary artery disease were examined but none was found to be of practical help. There was, however, a significant inverse relation between severity of coronary artery disease and severity of valve disease in patients with aortic valve disease. Asymptomatic coronary artery disease is not uncommon in patients with valvular heart disease and if it is policy to perform coronary artery bypass grafting in such patients, routine coronary arteriography must be part of the preoperative investigation.